Primary adenocarcinoma of the appendix in a child: A case report - Toshiaki Takahashi; Hiroshi Nouso; Masaya Yamoto; Koji Fukumoto; Naoto Urushihara (Surgical Case Reports)
Abstract Background Primary adenocarcinoma of the appendix is a rare disease in clinical practice. Moreover, primary adenocarcinoma of the appendix in the pediatric age group is even rarer with very little cases being published. Here, we report a case of primary adenocarcinoma of the appendix with local invasion into adjacent organs in a child who was initially diagnosed as having an acute appendicitis. Case presentation A 13-year-old girl presented with abdominal pain of 3-month duration. Imaging study showed a mass including the fecalith that occupied her pelvic and right lower abdominal cavity. Drainage of the abscess and appendectomy were performed by the preoperative diagnosis of an acute appendicitis with an appendiceal mass. Postoperative histopathological examinations revealed the appendiceal adenocarcinoma. She then received the whole mass resection, ileocecal resection with lymph node dissection. The masses were tightly adherent with infiltration into the sigmoid colon, uterus, and right ovary. These organs were all dissected, and subsequent sigmoid colostomy was performed. We preserved the left ovary for her fertility. The pathological findings demonstrated negative margins and no lymph node invasions, and final pathological stage was pT4(SI)N0M0, stage II. After the operation, she received the chemotherapy with 6 cycles of 5-fluorouracil (5-FU), leucovorin (LV), and oxaliplatin (mFOLFOX6) and subsequent 6 cycles of simplified LV and 5-FU (sLV5FU2). The patient is doing well till today on follow-up without progression of the disease 5 years after the operation. Conclusion Primary adenocarcinoma of the appendix is exceedingly rare in children. In this report, we described one of the youngest primary adenocarcinomas of an appendix case ever reported. When encountering atypical cases of the appendicitis, we should consider the possibility of primary adenocarcinoma of the appendix as it has an extremely poor prognosis and is usually diagnosed in advanced stages.